Cathedral of St. Paul and the United States Court House at Tremont Street, ca. 1875 - Unknown (Tufts Archival Research Center, 2005)
Street-level view south-southwest of the Cathedral of St. Paul and the United States Court House, located at 136 and 140 Tremont Street respectively. The facades of both buildings face west-northwest. The church is included near the left side of the photograph, and the courthouse is included near the right side of the photograph. Street lights line the sidewalk along Tremont Street, and a wrought iron fence encloses the grounds of the Cathedral of St. Paul. 2 7/8 x 3 Stereographs